The effectiveness of the SAVI method in improving poetry reading skills of elementary students - Abdul Latif; Septia Sugiarsih; Anwar Novianto (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study examines the effectiveness of the Somatic, Auditory, Visual, Intellectual (SAVI) learning method in enhancing the poetry reading skills of fifth-grade elementary school students. Employing a quantitative approach with a one-group pretest-posttest design, the research involved 36 fifth-grade students from Muhammadiyah Condongcatur Elementary School. Data were collected through structured observation sheets and analyzed using a paired sample t-test. The results indicate a statistically significant improvement in students' poetry reading skills following the intervention, with a significance value of 0.001 (< 0.05). The mean score increased by 30.72 points from pretest to posttest, demonstrating a substantial gain in performance. These findings lead to the conclusion that the SAVI method is an effective instructional strategy for significantly improving poetry reading proficiency in the target student population.